Peer support within academic seminars as a mechanism of academic socialization for international graduates - Ntirenganya, Theogene; Mugeni, Francoise; Uwizeyimana, Florien (Journal of International Students, 2026)
Academic seminars are pivotal to graduate education but are underexamined as sites of peer-mediated academic socialization, particularly beyond Western contexts. This qualitative case study explores how peer support within seminars facilitates the academic socialization of international graduate students in China. Drawing on Bandura’s social learning theory, peer support is conceptualized as a dynamic process of observation, modeling, and reciprocal engagement through which disciplinary norms are internalized. Triangulated data from 12 seminar observations, 10 semistructured interviews, and reflective journals were thematically analyzed. The findings indicate that seminars unfold across four structured phases—planning, presentation, discussion, and evaluation—in which peer support is embedded. Such interactions enhance psychological well-being by fostering a sense of belonging and mitigating isolation while advancing academic development through feedback, topic refinement, and improved scholarly writing. Seminars thus emerge as strategic pedagogical spaces for cultivating inclusive, collaborative, and socially grounded academic integration.